Association of lowering apolipoprotein B with cardiovascular outcomes across various lipid-lowering therapies: Systematic review and meta-analysis of trials. (1st August 2020) - Khan, Safi U; Khan, Muhammad U; Valavoor, Shahul; Khan, Muhammad Shahzeb; Okunrintemi, Victor; Mamas, Mamas A; Leucker, Thorsten M; Blaha, Michael J; Michos, Erin D
Abstract : Aims: The effect of therapeutic lowering of apolipoprotein B (apoB) on mortality and major adverse cardiovascular events is uncertain. It is also unclear whether these potential effects vary by different lipid-lowering strategies. Methods: A total of 29 randomized controlled trials were selected using PubMed, Cochrane Library and EMBASE through 2018. We selected trials of therapies which ultimately clear apolipoprotein B particles by upregulating low-density lipoprotein receptor (LDL-R) expression (statins, ezetimibe, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, bile acid sequestrants) or therapies which reduce apolipoprotein B independent of LDL-R (cholesteryl ester transfer protein inhibitor, fibrates, niacin, omega-3 fatty acids) with sample size of ≥1000 patients and follow-up of ≥1 year. The meta-regression and meta-analyses were constructed using a random effects model. Results: In 332, 912 patients, meta-regression analyses showed relative risks of 0.95 for all-cause mortality (95% confidence interval 0.92–0.99) and 0.93 (0.88–0.98) for cardiovascular mortality for every 10 mg/dL decrease in apolipoprotein B by all interventions combined. Reduction in all-cause mortality was limited to statins (0.92 (0.86–0.98)). For MACE, the relative risk per 10 mg/dL reduction in apolipoprotein B was 0.93 (0.90–0.97) for all therapies combined, with both statin (0.88 (0.83–0.93)) and non-statin therapies (0.96 (0.94–0.99)). which clear apolipoprotein B by upregulating LDL-R showing significant reductions; whereas interventions which lower apolipoprotein B independent of LDL-R did not demonstrate this effect (1.02 (0.81–1.30)). Conclusion: While both statin and established non-statin therapies (PCSK9 inhibitor and ezetimibe) reduced cardiovascular risk per decrease in apolipoprotein B, interventions which reduce apolipoprotein B independently of LDL-R were not associated with cardiovascular benefit.